Assessment of health-related quality of life in patients with adult onset Still disease: Results from a multicentre cross-sectional study. Issue 28 (15th July 2022) - Ruscitti, Piero; Rozza, Gelsomina; Di Muzio, Claudia; Biaggi, Alice; Iacono, Daniela; Pantano, Ilenia; Iagnocco, Annamaria; Giacomelli, Roberto; Cipriani, Paola; Ciccia, Francesco
Abstract : We aimed to investigate the health-related quality of life (HRQoL) in Adult onset Still disease (AOSD) patients, a rare systemic auto-inflammatory disorder of unknown etiology usually affecting young adults. In this multicentre cross-sectional study, AOSD patients and age and gender matched healthy controls (HCs) were included. All patients had a low or absent clinical expressiveness, they were categorized as having a monocyclic pattern or a chronic disease course. The Health Assessment Questionnaire (HAQ), European Quality of Life Questionnaire (EUROQoL), 36-Items Short-Form Healthy Survey (SF-36), Functional Assessment of Chronic Illness Therapy Fatigue subscale (FACIT-F), 100 mm-visual analogue scale (VAS) of pain, fatigue, and global health assessment, were used to evaluate HRQoL. The results were compared between patients and HCs, analyzed according to clinical course, and correlated with clinical features at the time of diagnosis. HRQoL resulted to be altered in 53 AOSD patients compared to 53 age and gender matched HCs. Many SF-36 domains differed between the 2 groups, mainly those of physical functioning which were reduced in AOSD respect to HCs. Furthermore, HAQ, FACIT-F, EuroQoL, VAS state of health, VAS pain, and VAS fatigue significantly differed between AOSD and HCs. No substantial differences were found comparing monocyclic pattern with chronic disease course. AOSD patients showed an impairment of many SF-36 domains, HAQ, FACIT-F, EuroQoL, VAS state of health, VAS pain, and VAS fatigue when compared to matched HCs, despite a low or absent clinical expressiveness; these findings were similarly retrieved in both monocyclic pattern and chronic disease course.